Evaluating the Extent Social Entrepreneurship Can Assist India’s Growth - Shrishail Biradar, Akshay (Digital Repository of Theses, 2025)
This dissertation examines the role of social entrepreneurship in fostering India's growth and development. As a transformative force, social entrepreneurship blends innovative and sustainable business models with a strong commitment to addressing pressing social challenges. With India facing multifaceted socio-economic issues despite significant economic growth, there is a need to explore alternative strategies that can effectively tackle these complexities. The research problem revolves around the potential of social entrepreneurship to contribute to India's growth and development. Traditional approaches to addressing social challenges have shown limitations, making social entrepreneurship a promising and innovative approach. By prioritizing social impact alongside financial viability, social entrepreneurs aim to create lasting social change, empowering marginalized communities and reducing social inequalities. The research employs in-depth interviews with social entrepreneurs, policymakers, and industry experts to gather insights into how social enterprises operate within the Indian context and their impact on local communities. Key themes examined include job creation, community empowerment, innovation, and the barriers faced by social enterprises in scaling their operations. Findings indicate that social entrepreneurship significantly contributes to India's growth by fostering inclusive economic development, creating employment opportunities, and promoting sustainable practices. However, challenges such as regulatory constraints, access to funding, and lack of awareness about social enterprises hinder their full potential. The significance of this research lies in its potential to inform policymaking, guide social entrepreneurs, inspire aspiring changemakers, contribute to academic knowledge, and create awareness within the broader community. Policymakers can benefit from insights into the effectiveness of social entrepreneurship, leading to targeted policies and support mechanisms. For social entrepreneurs, the research offers a roadmap and learning opportunities. Aspiring changemakers can gain inspiration and guidance from real-world examples. Academics will find valuable contributions to the growing field of social entrepreneurship research. The broader community can recognize the potential of social entrepreneurship as a viable approach to societal challenges.